FORMATION OF ECONOMIC COMPETENCE IN FUTURE SPECIALISTS IN THE CONDITIONS OF COLLEGE (Educological discourse, 2018)
The article reveals modern approaches to the formation of the economic competence of college students. The relevance and purpose of the research are formulated. The goal is to reveal the role of innovative teaching methods as one of the pedagogical conditions for the formation of economic competence among the applicants of education. The methods of scientific research were theoretical analysis of professional literature, pedagogical observation of the educational process, as the author of the article is a teacher of economic disciplines in college, another method of the research was a survey. The concept of «economic training» is defined, author's definition of the defined definition is given. It is an organized, systematic process for obtaining economic knowledge by college students, the formation of the practical skills and skills necessary for future activities and a set of values and norms aimed at the formation of an economic culture. On the basis of of scientists research works, the notion of «economic competence» is singled out as an integrative characteristic of a person, which includes knowledge and skills that are realized through economically important personality qualities in the process of economic activity. The author proposes the innovative approaches to the formation of economic competence in the process of studying specialized disciplines. Innovative teaching methods are developed, fragments of their application on lectures and practical classes are given. Such teaching techniques as Basket method, the Press method, the method of the incident, the method of nominal groups and others in the working practice at the economic college is described. It was investigated that economic competence was formed due to the subject and subject relations, the application of innovative teaching methods, which made it possible to acquire the values necessary for theprofessional activity. The conclusions and perspectives of further research are formulated.